Understanding Latino Student Racial and Ethnic Identification: Theories of Race and Ethnicity. Issue 1 (2nd January 2016) - Fergus, Edward
Abstract : The process of Latino self-identification, both racially and ethnically, is of limited conversation among educators. The research on Latinos focuses on either their ethnic construction or absence of including a racial identification. This article focuses on the span of research about ethnicity and race for Latino groups.